The Jurassic Thalattosuchia (Crocodyliformes) of Chile; a paleobiogeographic approach - Brandoni de Gasparini, Zulma Nélida (2000)
The thalattosuchian fossils from the Jurassic of Chile are revised. Some specimens, dating from the Lower Lias (Sinemurian), are the oldest known thalattosuchians, but are too fragmentary to establish a precise taxonomic placement. New specimen related to the genus Metriorhynchus is described from the lower Bajocian. It is the oldest representative of the genus and fills an important gap in our knowledge of the paleogeographic history of this group. Other new cranial fragments, related to the Callovian species Metriorhynchus casamiquelai, are described and this species is revised in the light of new studies on the intraspecific variability in extant crocodilians. Up until now, the known distribution of Liassic Thalattosuchia suggested a circumpacific distribution with minimally episodic passages through the Caribbean Corridor. Nevertheless, the close affinities between the South American and the European Metriorhynchidae from the Callovian to the Tithonian suggest the possibility that more and more frequent communications were made via the Caribbean Corridor. The new data corroborate the hypothesis formulated from the invertebrate faunas.